Comparative Analysis of Combined Topography-Guided Photorefractive Keratectomy and Corneal Crosslinking in Progressive Versus Stable Keratoconus - Gil, Pedro; Gil, João Quadrado; Dias, Margarida; Cunha, Bruna; Alves, Nuno; Rosa, Andreia; Murta, Joaquim (Cornea, 2025)
To perform a comparative analysis of visual, refractive, and tomographic outcomes of combined topography-guided photorefractive keratectomy (TG-PRK) and corneal crosslinking (CXL) in patients with progressive versus stable keratoconus. Longitudinal retrospective case-control study. Patients with keratoconus submitted to simultaneous TG-PRK and CXL were included, with a minimum follow-up of 12 months up to 3 years. According to predefined disease progression criteria, patients were considered as progressive or stable. A total of 101 eyes from 93 patients were included, 62 considered progressive and 39 stable keratoconus. All baseline characteristics were similar between groups, except for age at surgery (progressive: 23.40 ± 4.22 years; stable: 35.97 ± 9.09; P < 0.001). Logarithm of the minimum angle of resolution CDVA improved significantly in progressive (baseline: 0.48 ± 0.24; 12 months: 0.33 ± 0.29; P < 0.001) and stable (baseline: 0.51 ± 0.24; 12 months: 0.28 ± 0.21; P < 0.001) patients, with no differences between groups. Maximum keratometry decreased significantly in progressive (baseline: 59.18 ± 5.63 diopters; 12 months: 54.73 ± 5.95; P < 0.001) and stable (baseline: 57.77 ± 5.02; 12 months: 53.59 ± 4.20; P < 0.001) patients, with no differences between groups. Index of surface variance significantly improved in progressive (baseline: 109.18 ± 31.74 diopters; 12 months: 94.11 ± 34.11; P < 0.001) and stable (baseline: 102.87 ± 29.52; 12 months: 86.95 ± 27.21; P < 0.001) patients, with no differences between groups. Other tomographic outcomes were also similar between groups. Pachymetry significantly decreased after surgery but remained stable throughout the follow-up. Combined TG-PRK and CXL is a safe and effective procedure for improving CDVA and regularizing the cornea, with comparable visual, refractive, and tomographic outcomes in both progressive and stable keratoconus. Combined TG-PRK and CXL may be added to the armamentarium of therapeutic tools for visual rehabilitation in patients with stable keratoconus.